Generalized Theil-Tornqvist Indices with Applications to International Comparisons of Prices and Real Output - Rao, D. S. Prasada; Selvanathan, E. Anthony; Pilat, Dirk (The Review of Economics and Statistics, 1995)
D. S. Prasada Rao, E. Anthony Selvanathan, Dirk Pilat, Generalized Theil-Tornqvist Indices with Applications to International Comparisons of Prices and Real Output, The Review of Economics and Statistics, Vol. 77, No. 2 (May, 1995), pp. 352-360